A feces‐filled non‐inverted ileal pseudodiverticulum presenting as a pedunculated polyp successfully treated by traction‐assisted endoscopic submucosal dissection. Issue 1 (14th June 2022) - Inada, Taisuke; Sumida, Yorinobu; Ihara, Eikichi; Yoshitake, Chikako; Ohkubo, Akito; Tomoeda, Naru; Hamada, Shohei; Iboshi, Yoichiro; Nakamuta, Makoto; Harada, Naohiko
Abstract: A 68‐year‐old man was referred to our hospital for endoscopic treatment of colon polyps detected at a local clinic. Colonoscopy revealed not only classical adenomatous polyps in the transverse and sigmoid colon but also an atypical pedunculated polyp in the terminal ileum with the head of the lesion moving back and forth through the ileocecal valve. Based on the endoscopic findings, the pedunculated polyp was diagnosed as a non‐epithelial tumor of the ileum. However, traction‐assisted endoscopic submucosal dissection was performed because of the high risk of intestinal intussusception or obstruction. Histopathological analysis of the resected specimen revealed that the pedunculated polyp was a non‐inverted ileal pseudodiverticulum filled with feces. We report the first case of a feces‐filled non‐inverted pseudodiverticulum presenting as a pedunculated polyp successfully treated by traction‐assisted endoscopic submucosal dissection.